RELASI POLITIK DAN ADMINISTRASI DALAM KEPEGAWAIAN DAERAH - M.R. Khairul Muluk (Jurnal Manajemen Kepegawaian, 2009)
Relation in Politic and administration can be explained in two aspects: local government value and Personnel. Relation in first aspect is represented in debates between structural efficiency and local democracy model. Relation in second aspect is represented in struggle between value-free and value-laden approach. These relations put into continuum rather than dichtomy between politic and administration because both of them are viewed as complementary rather competition.Keyword: local government model, local government personnel, structural effeciency model, local democracy model, value-laden approach, value-free approach